Imunohistokimia S100 Dapat Mengidentifikasi Pola Kerusakan Saraf Tepi Pada Morbus Hansen Tipe Pausibasiler dan Multibasiler - Citra, Dandy; Sriwidyani, Ni Putu; Saputra, Herman (Perhimpunan Dokter Spesialis Patologi Anatomik Indonesia (PDSPA), 2025)
Background Morbus Hansen (MH) is a granulomatous infectious disease of the skin caused by Mycobacterium leprae, which induces skin lesions and peripheral nerve injuries that can cause physical disabilities. The basis of the diagnosis of MH is based on classic clinical signs, characteristic histopathological findings and demonstration of acid-fast bacilli in skin biopsies. However, determining neurovascular involvement in a granulomatous reaction is challenging in pathologic diagnosis. S100, a marker of pheripheral nerve, may aid MH diagnosis. The aim of this study to determine different pattern of S100 immunostaining in paucibacillary and multibacillary type MH. Methods This research was an analytic cross-sectional study. Sample was MH patients who underwent a skin biopsy and was examined for histopathology by routine H&E staining and Ziehl Neelsen (ZN) staining at the Anatomical Pathology Laboratory, Faculty of Medicine, Udayana University/Prof.Dr. I.G.N.G Ngoerah hospital, Denpasar from 2017 to 2022. Clinical information, histopathological examination results and ZN stain data were obtained. Pattern of neurovascular damage was determined by S100 immunohistochemistry and catagorized into intact infiltrated pattern and reduced/fragmented infiltrated patterns. The association between MH type and S100 staining pattern was analyzed by Chi-square test with a significance value of p<0.05. Results The results showed that the staining pattern in paucibaciler type MH was mostly reduced/fragmented infiltrated pattern, meanwhile in multibacillary type MH was mostly intact infiltrated pattern. There was a significant different S100 immunostaining pattern in Paucibaciler and Multibaciler MH (p=0.001). Conclusion S100 immunostaining can identify differences in staining patterns in cases of paucibacillary and multibacillary MH types. S100 may used as aditional testing to determine neurovascular involvement.